The impact of depressive symptoms on healthcare costs in late life: longitudinal findings from the AgeMooDe study - Bock, Jens-Oliver; Weyerer, Siegfried; Werle, Jochen (American journal of geriatric psychiatry, 2017)
Objective To examine whether depressive symptoms affect healthcare costs in old age longitudinally. Design Multicenter prospective observational cohort study (two waves with nt1 = 1,195 and nt2 = 951) in Germany. Setting Community. Participants Participants aged 75 years and older recruited via general practitioners.Measurements Depressive symptoms were assessed by the Geriatric Depression Scale (GDS). The health-related resource use was measured retrospectively from a societal perspective based on a questionnaire, covering outpatient services, inpatient treatment, pharmaceuticals, as well as formal and informal nursing care. Hybrid regression models were used to determine the between- and within-effect of depressive symptoms on healthcare costs, adjusting for important covariates. Results Six-month total cost increased from €3,090 (t1) to €3,748 (t2). The hybrid random effects models showed that individuals with more depressive symptoms had higher healthcare costs compared with individuals with less depressive symptoms (between-effect). Moreover, an intra-individual increase in depressive symptoms increased healthcare costs by €539.60 (within-effect) per symptom on GDS. Conclusions Our findings emphasize the economic importance of depressive symptoms in old age. Appropriate interventions to treat depressive symptoms in old age might also be a promising strategy to reduce healthcare costs.